Obtaining of strong chromium pellets with the use of a ferrosilicon-calcium binder - I. Bondarenko (Croatian Metallurgical Society, 2022)
The article presents the results of research on the synthesis of strong chrome pellets based on concentrates obtained by enrichment of chrome sludge. To obtain strong fired pellets from the concentrates, it is proposed to use a ferrosilico- calcium reagent as a binder, which makes it possible to increase the strength of the pellets by 2-3 times in comparison with the technology operating at “Donskoy Ore Mining and Processing Plant”. This excludes the supply of fluxing reagents during electric arc smelting of raw materials to high-carbon ferrochrome. Pellets from concentrates obtained during the processing of tailings from the Dubersay sludge storage have increased strength up to 5 330 N/pellet at a roasting temperature of 1 200 °C.